Neuroimaging features of MOPDII in ten patients with PCNT mutation: A Tertiary Centre Experience - Akalin, Akcahan; Gocmen, Rahsan; Simsek\\-Kiper, Pelin; Taskiran, Ekim; Alanay, Yasemin; Haliloglu, Vildan Goknur; Utine, Gulen Eda; Boduroglu, Koray (SPRINGERNATURE, 2024)
56th Annual Conference of the European-Society-of-Human-Genetics (ESHG), Glasgow, SCOTLAND, JUN 10-13, 2023